Development of Basic Mathematics Educational Game Based on Construct 3 as an Effective Interactive Learning Solution - Oula, Kiki Nabilah Pusvita; Permana, Basuki Rakhim Setya; Auliana, Sigit; Sunardi, Sunardi (PT ARRUS Intelektual Indonesia, 2024)
Game media as a learning medium in Indonesia does not have a long tradition. The image of games in the eyes of many people as a medium that can give the impression of entertainment compared to learning media, that's why the author decided to make a basic mathematics educational game. The purpose of this thesis proposal is 2, first to create an android-based basic mathematics education game application for children using construct 3, second to hone children's ability to calculate precisely with easy play. The type of research method used in making this educational game is Research and Development (R&D). This research process adapts the ADDIE development model according to Branch (2015), which is a development model consisting of five stages which include Analysis, Design, Development, Implementation, and Evaluation. The results of the research in this thesis proposal are producing basic mathematics educational games that focus on addition and subtraction material for children with an attractive display concept and easy way to play, this game can be accessed on Android smartphones.